2005
DOI: 10.1007/s00213-005-0137-x
|View full text |Cite
|
Sign up to set email alerts
|

Toluene exposure during the brain growth spurt reduces behavioral responses to noncompetitive N-methyl-d-aspartate receptor antagonists in adult rats

Abstract: These results indicate that neonatal but not adolescent toluene exposure produces long-term effects on selective behaviors induced by NMDA antagonists. Theses findings further support the hypothesis that functional changes in NMDA receptors may be related to the neurobehavioral dysfunction associated with fetal solvent syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…during the early postnatal period (postnatal day 4 (PN4) to PN9). These studies reported altered responses related to the glutamatergic system, with reduced hyperlocomotion induced by NMDA agonists ( Chien et al ., 2005 ), an increase in NR2A subunits in the hippocampus and cerebellum ( Lee et al ., 2005 ) and a decrease in NR2B levels (200–100 mg kg −1 i.p. from PN4 to PN7; Chen et al ., 2004 ).…”
Section: Developmental Issuesmentioning
confidence: 99%
“…during the early postnatal period (postnatal day 4 (PN4) to PN9). These studies reported altered responses related to the glutamatergic system, with reduced hyperlocomotion induced by NMDA agonists ( Chien et al ., 2005 ), an increase in NR2A subunits in the hippocampus and cerebellum ( Lee et al ., 2005 ) and a decrease in NR2B levels (200–100 mg kg −1 i.p. from PN4 to PN7; Chen et al ., 2004 ).…”
Section: Developmental Issuesmentioning
confidence: 99%
“…The oxidative stress hypothesis is supported by studies showing that the administration of antioxidants such as melatonin can counter the neurotoxic effects of toluene (Baydas et al, 2003; Pascual et al, 2010). In addition, because glutamatergic NMDA receptors play an important role in neural development and plasticity (Cull‐Candy et al, 2001) and because toluene administered during the preweaning period significantly altered NMDA receptor expression and function (Chen et al, 2005; Chien et al, 2005; Lee et al, 2005), it is possible that NMDA dysfunction may significantly contribute to the structural cell impairments observed in this and previous developmental studies. Moreover, considering that GABAergic transmission is significantly altered by the inhalation of volatile solvents such as toluene (MacIver, 2009), and that GABA plays an important role in neuronal development (Takesian et al, 2010), it is likely that this is an additional mechanism by which the abuse of inhalants can alter neuronal development and function.…”
Section: Methodsmentioning
confidence: 84%
“…The solvent‐induced reduction in brain weight and size is consistent with a previous study in which rat pups exposed to toluene between P4 and P10 displayed a dose‐dependent decrease in brain weight and astrocytic markers (Burry et al, 2003). Similarly, intraperitoneal toluene administration to rat pups at P4–P7 significantly reduced brain weight and caused glutamatergic dysfunction and neurobehavioral abnormalities (Chen et al, 2005; Chien et al, 2005). The data obtained in previous studies and in the present study are consistent with “fetal solvent syndrome”, which is found in human infants whose mothers were exposed to solvents during pregnancy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies support the notion that toluene is damaging to the developing brain, with one study in rats demonstrating a permanent reduction in forebrain myelination after prenatal exposure to toluene (Gospe & Zhou, 1998), while another found behavioral abnormalities in rats exposed to 95 96 M. TAKAGI ET AL. toluene postnatally during periods of high synaptogenesis (Bowen, Batis, Paez-Martinez, & Cruz, 2006;Chien, Chan, Tang, & Chen, 2005;Lubman, Yücel, & Lawrence, 2008; also see Cruz, in this issue).…”
Section: Introductionmentioning
confidence: 90%